PCR amplification of DNA microdissected from a single polytene chromosome band: a comparison with conventional microcloning. - Saunders, R D (1989)
A novel alternative to microcloning for the production of region specific chromosomal DNA is described. In this method, 'microamplification', single bands are dissected from polytene chromosomes and digested with Sau3A. Oligonucleotide adaptors are ligated to these fragments to provide convenient priming sites for polymerase chain reaction amplification. In this way, as much as 1 microgram of DNA can be amplified from a single band. Probes made from PCR amplified DNA from two such dissections have been used to probe cloned DNA form a 100 kb chromosome walk. Whereas conventional microcloning has generated cloned EcoRI fragments corresponding to 3-4 kb of the walk, the PCR probes cover greater than 90% of this chromosomal region. Thus microamplification is significantly more effective than microcloning in providing probes for establishing chromosomal walks.